AB0010 Angiogenesis Involved in Early Stages of Lupus Nephritis. (9th June 2015) - Mas, L.A.; Alvarellos, T.; Saurit, V.; De la Fuente, J.L.; Diller, A.; Caeiro, F.; Alvarellos, A.
Abstract : Background: Lupus Nephritis (LN) is one of the most frequent manifestations of SLE and can be present in 60% of SLE patients. It has been shown that structural changes and inflammatory infiltrate associated with LN contribute to a hypoxic state which induces angiogenesis [1]. Angiogenesis is a complex process that requires interaction between different cell types, the extracellular matrix, several cytokines and growth factors. Objectives: We proposed to study gene expression levels of angiogenic factors such as VEGF-A (Vascular Endothelial Growth Factor), VCAM-1 (Vascular cell adhesion molecule 1), TGF-β (Transforming Growth Factor), SEL-E (Selectin-E), ANGPT1 (Angiopoietin 1), AGT (Angiotensinogen) and END (Endostatin) in kidney biopsies from LN patients and their relationship with LN severity. Methods: Thirty two kidney biopsies samples were obtained from 32 LN patients and then classified according to ISN/RPS scoring system [3] in two groups, Class I/Class II biopsies (n=11, 10F/1M, age: 34.64±15.10, range: 21-72) and Class IV biopsies (n=21, 16F/5M, age: 30.95±11.36, range: 17-64). RNA was isolated using TRIzol-Chloroform technique and then was reverse-transcribed using random primers. Gene expression level of pro-angiogenic factors: VEGF, VCAM-1, TGF-β, SEL-E, ANGPT-1 and anti-angiogenic factors: AGT and END were evaluated using Quantitative Real Time PCR (QPCR). The threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting β2Microglobuline (β2M) control, or ΔCt=Ct, gene - Ct, B2M . To test for differential gene expression between groups, a two sample T-test was performed to compare the ΔCt in the two groups. Results: ΔCt is inversely proportional to the gene expression level. Significant differences between groups were found in pro-angiogenic genes VEGF-A (p=0, 05), VCAM-1 (p=0, 05) and in anti-angiogenic gene END (p=0, 05) (Table 1 ). There were not statistically significant differences in the expression of AGT, ANGPT-1, SEL-E and TGF-β between groups. After T test, we evaluated data from ΔCt analysis observing that the levels of mRNA of VEGF-A and VCAM-1 in Class I/II group were higher than those from Class IV group. Conversely, END gene expression was decreased in Class I/II group. Conclusions: In the present cross-sectional study, increased levels of VEGF-A and VCAM-1 and decreased levels of END were observed in biopsies classified as Class I and II. These findings could be associated with angiogenesis process in early stages of the disease. Angiogenesis in progression to LN deserves further evaluation. References: Feliers D. Vascular Endothelial Growth Factor as a prognostic marker of Lupus Nephritis. Kidney Int; 75:1251-1253. 2009. Weening JJ. et al. The classification of glomerulonephritis in systemic lupus erythematosus revisited. Kidney Int: 65 (2):521-30. 2004. Disclosure of Interest: None declared